Use of pharmacoinvasive approach to the treatment of patients with ST segment elevation acute coronary syndrome: state of the problem - S. R. Gilyarevskiy; M. V. Golshmid; I. M. Kuz'mina (Столичная издательская компания, 2015)
Role of pharmacoinvasive tactics in the treatment of patients with ST-segment elevation acute myocardial infarction is considered. The expert opinions reflected in the final version of the guideline are given, as well as the results of clinical trials in which the efficacy of thrombolytic therapy at early stage after acute myocardial infarction onset compared with primary percutaneous coronary intervention. The place of pharmacoinvasive tactics in real clinical practice is discussed.